A simple technique for suspension and stabilization of retrieval bag and adnexa by anchoring to the abdominal wall - Ioannis Chatzipapas (Wiley, 2021)
Abstract We describe a useful technique, in laparoscopic cystectomy in‐a‐bag, for suspension and stabilization of endobag and adnexa using temporary sutures. It intends to create an isolated field to avoid spillage of the cyst content into the abdomen in case of rupture, thereby allowing the safe laparoscopic removal of ovarian masses.